An EFL Teacher's Perspective on The Implementation of Formative Assessment - Ismi Reza Karomah Karomah; Istanti Hermagustiana; Widia Anggraeny Suharno (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2026)
This research explored the perspectives of an English as a Foreign Language (EFL) teacher regarding the implementation of formative assessment in teaching-learning activities in the classroom. This research also identified the personal and contextual factors that influenced the teacher’s perspectives. The subject of this research was a teacher from SMPN 17 Balikpapan who had an undergraduate educational background, had completed a teaching certificate program, and had implemented formative assessment for more than two years. This research used a qualitative case study design as its approach. The data were gathered through semi-structured interviews, classroom observations, and document analysis. Methodological triangulation was used to validate the data by cross-checking the interview transcripts, observations, and document analysis results. The findings revealed that the EFL teacher was proactive in viewing formative assessment as an ongoing evaluation process and was aware of the importance of its function, which extended beyond an administrative requirement to helping students achieve learning objectives. Since students were placed at the center of the learning activities, formative assessment functioned as a compass to determine whether the learning process followed the lesson plan, required adjustments, or needed to be changed entirely. This perspective was shaped by personal factors, such as the teacher’s educational background, beliefs, and attitudes, as well as contextual factors, including the school environment, working conditions, and students’ characteristics.